TRANSFORMATION OF VALUES OF THE HIGH TECHNOLOGY PROJECTS FROM A VUCA TO A BANI ENVIRONMENT MODEL - Bushuyev, Sergiy; Piliuhina, Kateryna; Chetin, Elams (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The article is dedicated to the study of impact of a BANI-world conditions to implementation of the high technology industrial projects and in particular of the nuclear industry projects. The purpose of the article is to analyze tendencies of changes of different factors related to the high technology nuclear project implementation against the changing conditions of the environment. The object is the project management methodologies in the BANI environment. The subject is theoretical analysis of the values differentiation in between the VUCA and BANI worlds, key aspects of BANI impacting implementation of the nuclear projects. Tasks to be solved: to analyze the transformation from the VUCA model to the BANI model, to present values and their differentiation as the basis for survival in the new world order, to develop a method for assessing project risks in the BANI environment. Methods: practical empirical analysis of nuclear project risks in comparison with BANI-model forecasts, applied research, project risk management methodology, probability theory. The following results were obtained: the differences between the values of s VUCA and BANI are determined, an understanding of the general changes that have arisen due to the functionality of the environment is provided, the project management methodology applicable in the BANI environment is analyzed, a qualitative and quantitative risk analysis based on BANI projections is implemented on the example of a nuclear project in Ukraine, and the grounds for determining the most influential BANI forecast are proposed. The main results of the research are identification and analysis of values and their differentiation in the process of transformation from the VUCA to the BANI world, proposals for the project management approach which could cover the needs of the nuclear project and the consequences of this transformation. To estimate risks, it was proposed to use qualitative and quantitative methods of risk assessment. The case study of one of the nuclear projects in Ukraine, and a mixed classic-Agile methodology for the management of the nuclear project was performed. Conclusions: risk management of the nuclear projects has to be carried out based on the impact of the BANI-projections to identified risks.